A Political Opportunity Structure Analysis for the Recognition of Palestinian Statehood by European Countries - Hasbi Aswar; Rizki Dian Nursita; Emil Hikmawan; Zahara Aini Fijria Azzuhro (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2026)
This study elaborates the impact of the recognition of Palestinian statehood by several European countries for the development of pro-Palestinian movements in the region. This study uses political opportunity structure in social movement studies as the theoretical framework to highlight how formal political support from European states creates a greater space for pro-Palestinian movements to mobilize within Europe. A media-based qualitative method is used to collect the data by tracing news coverage, discourse, and public opinion across major online media platforms in Europe. The study finds that the increased recognition of Palestine among European countries enhances the legitimacy of pro-Palestinian movements and creates opportunities for the changing narratives that are more objective and sympathetic toward the Palestinian issue. This is significant given that dominant narratives in Europe have long favored Israel. Hence, the political recognition of Palestine by European states contributes to the reconfiguration of public discourse while simultaneously strengthening the political position of pro-Palestinian movements within Europe's political and social arenas.